Actualization of Symbolic Values in the Marriage Series Mandar Customs in Polewali Mandar Regency (Perspective of Muhammad Syahrur's Hudud Theory) - Karmuji; Hannani; Agus Muchsin (Universitas Muhammadiyah Palu, 2023)
This research aims to explore the stages of marriage in the Mandar community in Polewali Mandar Regency, delve into the symbolic values contained in the Mandar traditional wedding symbols in Polewali Mandar Regency, and examine marriage in Polewali Mandar Regency based on the perspective of Hudud Theory by Muhammad Syahrur. The research method used is qualitative, with a phenomenological approach to the natural conditions found within the research object. The research instrument consists of a questionnaire given to informants, including Cultural Experts, Religious Figures, Community Leaders, and Youth Leaders in Polewali Mandar Regency. The data analysis includes data analysis, data reduction, and conclusion. This research indicates that the stages of marriage in the Mandar community in Polewali Mandar Regency consist of sixteen traditional practices still being practiced. These traditional practices include: Mambala'ba, Messisi, Mettumae, Pappasa'bi, Manjanno-janno, Mattandajari, Mappapeissang, Messou, Melattigi, Metindor, Sipacu, Sirusa'i, Suyu', Me'oro tosiala, Mande-ande Kaweng, and Massiarai ku'bur. The symbolic values contained in the Mandar traditional wedding symbols generally align with the principles of Islamic teachings, but certain aspects still require adjustments, such as the standing competition, which implies that the one who stands up first will have authority in the household. This contradicts the essence of the purpose of marriage. The perspective of Hudud Theory by Muhammad Syahrur in viewing marriage is divided into two parts: 1) Islamic marriage, where the Mandar community still adheres to the boundaries set by religion, and 2) Mandar traditional marriage, which remains within the boundaries of Mandar customary practices and does not contradict religious teachings.